Desenvolvimento da figueira (Ficus carica L.) em diferentes coberturas de solo na transição Cerrado-Amazônia - Pizzatto, Mariana (2023)
The fig plant (Ficus carica L.) belongs to the family Moraceae and has easy adaptation to different edaphoclimatic conditions. Considering the productive potential of the fig tree, it was aimed to evaluate the physiological responses of young fig plants, intercropped with green cover plant species, as well as to determine the crop coefficients, crop evapotranspiration and water use efficiency in different mulches in the Cerrado-Amazon transition. To this end, the first chapter evaluated the effects of the "green cover crop" consortium on physiological responses in leaves of young fig plants. The fig trees were in the eighth month of intercropping with the species Brachiaria ruziziensis (BR), mucuna-preta (MP), feijão-guandu (FG) and estilosantes (ES) and without intercropping (SC). The characteristics of leaf gas exchange and chlorophyll A fluorescence were determined by dividing the leaves along the plant into apical, middle and basal sections, with six repetitions in an entirely randomized design. No interaction was observed between the consortia and the position of leaf insertion in the plant. The photosynthesis of the leaves of fig tree roxo-de-valinhos in the Cerrado-Amazon transition is 8.04 to 11.55 µmol m-2s-1. The apical leaves show higher net photosynthesis 11.47 µmol m- 2s-1 higher electron transport rate 73.32, however they obtained lower maximum quantum yield of PSII (0.73). In chapter two, the crop evapotranspiration (ETc), crop coefficients (Kc) and water use efficiency of fig tree under different dead covers were determined. The work was developed in two consecutive dry seasons, when the plants were in the canopy formation phase with two and eight productive branches, in the years 2020 and 2021 respectively, using 2.5 kg m-2 of BR, MP, FG and Emerald Grass (GE) straw and no mulch (SC) in causalized blocks with three repetitions. The different mulches had little influence on ETc, Kc in both crop years; however, in the year 2021, the values were higher, due to the developmental stage of the plants. The cultivation of fig tree with BR mulch, in the second year, allowed obtaining 2.59 kg of ripe figs per m3 of effective water blade, while only 0.79 kg per m3 were obtained in SC plants. The use of Brachiaria ruziziensis grass, either intercropped with young plants or used as mulch on adult fig plants is the best technical option for the development of roxo-de-valinhos cultivar in the Cerrado-Amazon transition.